2017
DOI: 10.1007/s11128-017-1516-z
|View full text |Cite
|
Sign up to set email alerts
|

Perfect state transfer by means of discrete-time quantum walk on complete bipartite graphs

Abstract: We consider a quantum walk with two marked vertices, sender and receiver, and analyze its application to perfect state transfer on complete bipartite graphs. First, the situation with both the sender and the receiver vertex in the same part of the graph is considered. We show that in this case the dynamics of the quantum walk is independent of the size of the second part and reduces to the one for the star graph where perfect state transfer is achieved. Second, we consider the situation where the sender and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 53 publications
(97 reference statements)
0
38
0
Order By: Relevance
“…The phenomenon of perfect state transfer (PST) in quantum communication networks was originally introduced by Bose in [14]. This work has attracted much research interest since many applications have been found in quantum information processing and cryptography (see [1,2,3,5,11,15,17,18,34,38,37] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of perfect state transfer (PST) in quantum communication networks was originally introduced by Bose in [14]. This work has attracted much research interest since many applications have been found in quantum information processing and cryptography (see [1,2,3,5,11,15,17,18,34,38,37] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…For our selection of initial coins, (20) simplifies to F bound ±π/2,0 = 1 − λ 2 ± . The localisation region apparent in figure 3(a), when φ ∈ (π/2, 2π), is directly related with F bound −π/2,0 shown in figure 3(b).…”
Section: Bound State Localisationmentioning
confidence: 99%
“…Furthermore, the whole graph G might be encoded in an oracle representing the search space and, thus, inaccessible to us. We can draw some information from the works [26][27][28], where an analogy between searches and state transport is investigated. In similar way we shall explore the possibility of starting on one of the connections and observe "transport" of the state to the neighboring connections.…”
Section: Evolution Of a Localized State On A Ring Of Starsmentioning
confidence: 99%
“…A more recent use of quantum walks is in state transfer [26][27][28]. One has two distinguished vertices in a graph.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation